Risks and complications of tourniquet syndrome in blast injuries in the context of contemporary military conflicts - V. V. Chorna; G. V. Osyodlo; S. M. Stadnik; K. V. Savichan; V. M. Lipkan; V. V. Kolomiets; M. V. Rybinskyi; S. Yu. Nesterova; L. S. Hudzevych (Український журнал військової медицини, 2025)
The purpose was to analyze the impact of the use of tourniquets by military personnel during massive or critical bleeding, as well as in cases of traumatic amputations of limbs. Special attention is devoted to the timely conversion of the tourniquet, determining the feasibility and inappropriateness of its use, assessing the duration of its application, and analyzing complications arising from excessively long use, especially in conditions of intense hostilities or prolonged evacuation.